A Retrospective Analysis of Scorpion Envenomation Cases Treated in Rozhhalat Emergency Hospital Erbil City in 2018 - Mohammed K. Raqeeb; Halgurd Fathul; Soran Ahmad (Academic Journal of Clinicians, 2022)
Scorpion sting cases are frequently presented to emergency departments. The definite epidemiology and clinical characteristics of these cases in Kurdistan are still vague. To assess demographical data on scorpion envenomation cases, the treatment given and the complications and the outcome of envenomation in Rozhhalat Emergency Hospital, Erbil city of Kurdistan. This is a retrospective cross sectional review conducted in Rozhhalat Emergency Hospital in Erbil, Kurdistan Region of Iraq. The study duration is one year, from 1st of January to 31st of December 2018, on 147 patients with scorpion sting. The diagnosis of scorpion sting is made by the Emergency Physician according to the history of the sting and clinical examination findings. The severity of scorpion envenomation is measured according to clinical findings and complications. Our findings revealed a mean age of patients with scorpion sting in this study is (35.3 years), 45.6% of them are in age group of 18-64 years with female gender predominance. The lower extremity is the prevalent anatomical site and 19.7% of patients presented to the emergency department within one hour after the sting. Generally, the vital signs and examination findings are abnormal in a low proportion of patients with scorpion sting, however, 69.4% of them had local pain. Only one patient is categorized at grade IV of scorpion envenomation. The patients are treated by analgesia, antihistamines, steroids and 31.9% of them are treated with antivenin. All studied patients are alive and only one patient needed admission to intensive care unit. In conclusions: The majority of scorpion sting patients presented to the emergency department in Erbil are mild cases